A Multisectoral Strategy for Expanding JKN Coverage: Policy Analysis and Implementation Framework - Ni Luh Ayu Citra Mutiarahati; Luh Verra Sridayantari (Bali Medical and Wellness Journal, 2025)
Background: The National Health Insurance (JKN) program aims to achieve universal health coverage (UHC) in Indonesia. Although participation rates have increased from year to year, data shows that around 27.8% of Indonesia's population still do not have valid health insurance. The biggest challenges are faced by areas with difficult geographical conditions such as Papua, Maluku, and parts of Sumatra. Objects: This article analyzes the multisectoral approach as a strategy to expand the coverage of JKN. Method: Using qualitative methods through literature review and policy analysis, findings show that cross-sector engagement including local government, education, social, and community sectors contributes significantly to expanding coverage. Results: The results of the analysis show that an integrated multi-sectoral strategy, adaptive to the local context, and supported by synergistic regulations is the key to accelerating the achievement of Universal Health Coverage (UHC) in Indonesia. Conclusion: Recommendations include administrative strategies in the form of Strengthening cross-sectoral governance and harmonization of regional health insurance policies to facilitate coordination between the central and regional governments. Community-Based Strategy: Involving local communities in socialization and increasing community participation in the JKN program. and Technology Strategy: Data integration and utilization of information technology to facilitate registration and increase access to health services, especially in remote areas.